Clinical research in ovarian cancer: consensus recommendations from the Gynecologic Cancer InterGroup. Issue 8 (August 2022) - Vergote, Ignace; Gonzalez-Martin, Antonio; Lorusso, Domenica; Gourley, Charlie; Mirza, Mansoor Raza; Kurtz, Jean-Emmanuel; Okamoto, Aikou; Moore, Kathleen; Kridelka, Frédéric; McNeish, Iain; Reuss, Alexander; Votan, Bénédicte; et al.
Summary: The Gynecologic Cancer InterGroup (GCIG) sixth Ovarian Cancer Conference on Clinical Research was held virtually in October, 2021, following published consensus guidelines. The goal of the consensus meeting was to achieve harmonisation on the design elements of upcoming trials in ovarian cancer, to select important questions for future study, and to identify unmet needs. All 33 GCIG member groups participated in the development, refinement, and adoption of 20 statements within four topic groups on clinical research in ovarian cancer including first line treatment, recurrent disease, disease subgroups, and future trials. Unanimous consensus was obtained for 14 of 20 statements, with greater than 90% concordance in the remaining six statements. The high acceptance rate following active deliberation among the GCIG groups confirmed that a consensus process could be applied in a virtual setting. Together with detailed categorisation of unmet needs, these consensus statements will promote the harmonisation of international clinical research in ovarian cancer.